Postpartum Maternal Care Tradition in Manunggang Jae Village Padangsidimpuan City Indonesia - Rosmala Dewi; Ida Yustina; Etti Sudaryati; Nurmaini; Fikarwin Zuska (Britain International for Academic Research (BIAR) Publisher, 2020)
Maternal and child health problems cannot be separated from cultural factors in the society. One example of culture related to maternal and child health is the marapi tradition carried out by the puerperal mother in Manunggang Jae Village, Padangsidimpuan City. Marapi tradition is a tradition of fumigating or heating a mother who has just given birth and her baby for 40 days. This study aims to explore more information about the practice of postpartum maternal care in Manunggang Jae Village, Padangsidimpuan City. This research is a qualitative research with phenomenology design. Data collection was conducted through in-depth interviews with 8 postpartum mothers, traditional leaders and health workers in October 2018 untill August 2019 in Manunggang Jae Village, Padangsidimpuan City. The results showed that postpartum maternal care was based on hereditary traditions, the types of care were fumigation of the mother and baby during puerperium and standing on a fireplace (manjonjongi api). The community believes this practice makes mothers recover faster and babies are stronger but in terms of health this tradition has a negative impact on the health of postpartum mothers and newborns.